Prediabetes relates to impaired mitochondrial function in human ventricular myocardium. (3rd October 2022) - Zweck, E; Scheiber, D; Schultheiss, H P; Kelm, M; Roden, M; Szendroedi, J; Westenfeld, R
Abstract: Background/Introduction: With the growing prevalence of prediabetes in developed countries, complications of this predecessor of diabetes mellitus type 2 become increasingly important for medical research and practice. Prediabetes is defined as impaired fasting glucose (IFG) and/or impaired glucose tolerance (IGT) and may also incorporate elevated hemoglobin A1. While overt type 2 diabetes is a well-established risk factor and can even be the cause of cardiac failure, this is not yet proven for prediabetes. Mitochondrial impairment is a key pathomechanism in heart failure, but it remains uncertain, whether prediabetes impairs myocardial energy metabolism in humans just as type 2 diabetes does. Purpose: We aimed to scrutinize the impact of prediabetes on myocardial mitochondrial metabolism and cardiac function. Methods: We included 50 heart transplant recipients with normal glucose tolerance (GT, n=25), prediabetes (n=8, 3 IFG and 5 IGT) or type 2 diabetes mellitus (T2DM, n=17), who had received a healthy donor heart from a non-diabetic donor. In this cohort, the impact of the recipients' metabolism should be displayed in the donor heart after transplantation. We performed oral glucose tolerance tests to assess the diabetes status, and cardiac magnetic resonance imaging to assess cardiac systolic and diastolic function, circulating biomarkers of oxidative stress in serum samples (thiobarbituric acid reactive substances (TBARS) and redox potential), as well as global T2 relaxation times as a marker of myocardial inflammation. In transcatheter endomyocardial biopsies, we assessed myocardial mitochondrial oxidative capacity using high-resolution respirometry and myocardial mRNA expression of nuclear factor kappa B p105 subunit (NFKB1). Results: GT and IFG/IGT patients exhibited comparable demographic and clinical characteristics, whereas T2DM had higher BMI, glycemia, triglycerides and creatine kinase (all p<0.05). None of systolic (p=0.99), diastolic cardiac function (p=0.81), myocardial NFKB1 expression (p=0.74), circulating oxidative stress markers (p=0.94 and 0.95) or cardiac T2 relaxation times (p=0.99) were altered in IFG/IGT compared to GT, but diastolic strainrate was impaired (p=0.03) and circulating oxidative stress (TBARS: p=0.03, redox potential: p=0.04) were higher in T2DM than in GT. However, myocardial mitochondrial function stood out to be already impaired in IFG/IGT to a similar extend as in T2DM. This particularly applied to substrates of mitochondrial complex I (GT vs. IFG/IGT vs. T2DM: 126±7 vs. 89±12 vs. 93±6 pmol s –1 mg –1 . p=0.02) and II (188±13 vs. 123±17 vs. 138±11 pmol s –1 mg –1 . p=0.02). Intrinsic uncoupling was not altered in IFG/IGT but tended to be higher in T2DM (leak control ratio: 0.49±0.02 vs. 0.46±0.06 vs. 0.57±0.04 [arbirary units]). Conclusion: Our findings point towards mitochondrial impairment as a predecessor of overt heart failure in prediabetes and may represent an early footprint of prediabetic cardiomyopathy. Funding Acknowledgement: Type of funding sources: None.